Fluoroscopy-Guided High-Intensity Focused Ultrasound Neurotomy of the Lumbar Zygapophyseal Joints: A Clinical Pilot Study. Issue 1 (17th September 2021) - Perez, Jordi; Gofeld, Michael; Leblang, Suzanne; Hananel, Arik; Aginsky, Ron; Chen, Johnny; Aubry, Jean-Francois; Shir, Yoram
Abstract: Objective: To investigate the safety and feasibility of a fluoroscopy-guided, high-intensity focused ultrasound system for zygapophyseal joint denervation as a treatment for chronic low back pain. Methods: The clinical pilot study was performed on 10 participants diagnosed with lumbar zygapophyseal joint syndrome. Each participant had a documented positive response to a diagnostic block or a previous, clinically beneficial radiofrequency ablation. For a descriptive study, the primary outcome was the safety question. All device- or procedure-related adverse events were collected. Secondary outcome variables included the average numeric rating scale for pain, the Roland-Morris Disability Questionnaire, the Brief Pain Inventory, the Patient Global Impression of Change, the morphine equivalent dose, and the finding of the neurological examination. Results: All participants tolerated the procedure well with no significant device- or procedure-related adverse events; there was one episode of transient pain during the procedure. The average numeric rating scale score for pain decreased from 6.2 at baseline to 2.1 (n = 10) after 1 month, 4.9 (n = 9) after 3 months, 3.0 (n = 8) after 6 months, and 3.0 (n = 6) after 12 months. The ratio of participants who were considered a treatment success was 90% at 1 month, 50% at 3 months, 60% at 6 months, and 40% at 12 months. Conclusions: The first clinical pilot study using a noninvasive, fluoroscopy-guided, high-intensity focused ultrasound lumbar zygapophyseal neurotomy resulted in no significant device- or procedure-related adverse events and achieved clinical success comparable with that of routine radiofrequency ablation.